An Intrinsic Hydrophobicity Scale for Amino Acids and Its Application to Fluorinated Compounds. Issue 24 (10th May 2019) - Hoffmann, Waldemar; Langenhan, Jennifer; Huhmann, Susanne; Moschner, Johann; Chang, Rayoon; Accorsi, Matteo; Seo, Jongcheol; Rademann, Jörg; Meijer, Gerard; Koksch, Beate; Bowers, Michael T.; von Helden, Gert; et al.
Abstract: More than 100 hydrophobicity scales have been introduced, with each being based on a distinct condensed‐phase approach. However, a comparison of the hydrophobicity values gained from different techniques, and their relative ranking, is not straightforward, as the interactions between the environment and the amino acid are unique to each method. Here, we overcome this limitation by studying the properties of amino acids in the clean‐room environment of the gas phase. In the gas phase, entropic contributions from the hydrophobic effect are by default absent and only the polarity of the side chain dictates the self‐assembly. This allows for the derivation of a novel hydrophobicity scale, which is based solely on the interaction between individual amino acid units within the cluster and thus more accurately reflects the intrinsic nature of a side chain. This principle can be further applied to classify non‐natural derivatives, as shown here for fluorinated amino acid variants. Abstract : A matter of scale : The size and shape of gas‐phase clusters have been used to classify natural and fluorinated amino acids according to their intrinsic hydrophobicity. This new hydrophobicity scale is based solely on the interaction between individual amino acid units within the cluster and thus more accurately reflects the intrinsic nature of a side chain than other scales.